(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
Nouns is the 3rd declension, a group of words comprising all three genders and showing a great diversity of form. Your first reaction may be one of dismay, since this declension has no consistent word-ending, like the -a, -us, and -um of the 1st and 2nd, and appears to have little predictability of any kind. You’ll soon learn that the situation is really not that chaotic, since the 3rd declension does operate on regular and consistent principles.